2010
DOI: 10.1128/mcb.00521-10
|View full text |Cite
|
Sign up to set email alerts
|

Lysine-Specific Demethylase 1 Regulates the Embryonic Transcriptome and CoREST Stability

Abstract: Lysine-specific demethylase 1 (LSD1), which demethylates mono-and dimethylated histone H3-Lys4 as part of a complex including CoREST and histone deacetylases (HDACs), is essential for embryonic development in the mouse beyond embryonic day 6.5 (e6.5). To determine the role of LSD1 during this early period of embryogenesis, we have generated loss-of-function gene trap mice and conditional knockout embryonic stem ( The methylation of lysine residues within histones H3 and H4 helps to regulate the higher-order st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
185
3
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(200 citation statements)
references
References 62 publications
11
185
3
1
Order By: Relevance
“…1b for schematic of the different embryonic cell types). Consistent with previous reports [19][20][21][22] , we find that Lsd1 À / À embryos are significantly reduced in size but possess cells of the three early embryonic lineages, namely epiblast, extraembryonic ectoderm and primitive endoderm/visceral endoderm as shown by haematoxylin and eosin (HE) staining (Fig. 1b).…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…1b for schematic of the different embryonic cell types). Consistent with previous reports [19][20][21][22] , we find that Lsd1 À / À embryos are significantly reduced in size but possess cells of the three early embryonic lineages, namely epiblast, extraembryonic ectoderm and primitive endoderm/visceral endoderm as shown by haematoxylin and eosin (HE) staining (Fig. 1b).…”
Section: Resultssupporting
confidence: 81%
“…To specifically dissect Lsd1 functions in the different cell lineages of the pregastrula stage mouse embryo, we engineered a novel conditional Lsd1 allele by flanking exon 1 with loxP sites. In agreement with earlier reports [19][20][21][22] , ubiquitous deletion of the conditional Lsd1 allele (Lsd1 À / À ) leads to early embryonic lethality, and only resorbed embryos are detected by E7.5 (Fig. 1a).…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…Epigenetic intervention and/or HDAC inhibition have been recently identified as the critical determinant for cell programming in in vitro studies (16, 42, 44). Although we have (9,11,24,32). In this study, using the established siRNA approach, which is widely performed to knockdown specific genes in progenitor cells (17), we demonstrated that the treatment of HDAC4 siRNA significantly induced the knockdown of HDAC4 in c-kit ϩ CSCs, which is also accompanied by the reduction of HDAC activity.…”
Section: Discussionmentioning
confidence: 95%